A follow up study on lung cancer survival in the state hospital in east coast state of Pahang - Balakrishnan, Sivasubramaniam; Ab Rahman, Jamalludin; Koya kutty, Shaheedah; Abdul Razak, Megat Razeem; Ibrahim, Aishah; How, Soon Hin (IIUM, 2025)
INTRODUCTION: There is lack of data of lung cancer survival in Malaysia. MATERIAL AND METHODS:This study was to determine the survival of lung cancer patients andfactors affecting the survival in Kuantan, Pahang. A total of 170 lung cancer patientsconfirmed by histology from 1st January 2014 to 31 December 2017 were recruited inthe study. Their demographic data, ECOG performance status, staging and treatmentwere recorded. Survival time was defined in weeks from the date of histologicaldiagnosis made to the date of death of the patients. Kaplan-Meier curve was used todetermine the median overall survival and log-rank test was used to test the survivaldifferences between each subgroup. Multivariate analysis using COX regression wasused to determine factors affecting its survival.RESULTS: The median age of the170 patients was 63 years old, majority were males (74%) and smokers (64%).Adenocarcinoma (74.7%) was the most common histology followed by squamous cellcarcinoma (18.8%). Almost all patient presented at the clinic at stage 3 or 4 (98%) butmajority had ECOG 0-2 (64.3%). Median overall survival was 28.7 weeks. In themultivariate analysis, “supportive treatment” and “poor ECOG performance status”were independent predictors of death with thehazard ratio of 1.4 (95%CI 1.17 to 1.66)and 3.0 (95%CI 2.05 to 4.39) times respectively.CONCLUSION: Majority of lungcancer patients in Pahang presented with advanced disease with overall median survivalof 28.7 weeks. Patients treated with supportive care and poor ECOG performancestatus were the two independent poor prognostic factors for survival.